Complex electronic structure and compositing effect in high performance thermoelectric BiCuSeO - Guang-Kun Ren (Nature Portfolio, 2019)
Though BiCuSeO is a promising thermoelectric material, further study of its electronic structure-property relationship and compositing effect is required to optimize the performance. Here, the authors observe three power factor maxima in BiCuSeO with the increasing Pb-doping content.